A VO2 based hybrid super-capacitor utilizing a highly concentrated aqueous electrolyte for increased potential window and capacity. (10th June 2020) - Lindberg, Simon; Ndiaye, Ndeye Maty; Manyala, Ncholu; Johansson, Patrik; Matic, Aleksandar
Abstract: In this work we demonstrate the application of a highly concentrated aqueous electrolyte to a hybrid supercapacitor cell. We combine an 8 m Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) aqueous electrolyte with a nanostructured VO2 -cathode to enhance the voltage widow up to 2.4 V in a full cell. With the enhanced potential window, we are able to exploit the full contribution of the VO2 material, where a part is outside the stability window of standard alkaline aqueous electrolytes. We show that the VO2 material in the highly concentrated electrolyte provides a faradaic contribution even at the highest current density (25 A/g) and in this way increases the energy content also in high power conditions. The full cell shows a good efficiency but also a capacity fade over 500 cycles (39%) which is most likely related to dissolution of VO2 .